2015
DOI: 10.1002/asia.201501127
|View full text |Cite
|
Sign up to set email alerts
|

Pentannulation of Heterocycles by Virtue of Precious Metal Catalysis

Abstract: Pentannulated heterocycles are the key structural subunit of many natural and biologically active compounds. Over the last decades, many precious metal-assisted pentannulations have been described as a consequence of an extensive research. This Focus Review gives an overview of precious metal-catalyzed reactions applied to the synthesis of cyclopenta-fused heterocycles in the last five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…[24][25][26] This being said, the gamut of application of gold catalysis is quite comprehensive to cover the synthesis of an array of important commodities like natural products, [27][28][29][30][31][32][33][34][35] drugs [36] and polymers. [37,38] Gold complexes have been documented to exhibit versatile catalytic efficiency towards a plethora of organic reactions such as CÀ H activation, [39][40][41][42][43] substitution, [44] cycloaddition, [45][46][47][48][49][50] oxidative coupling, [51,52] hydration, [53,54] oxidation, [55][56][57] hydroamination, [58,59] nucleophilic addition, [60] hydrogenation, [61] cross-coupling, [62,63] carbocyclization, [64] heterocyclization, [65][66][67][68][69][70]…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] This being said, the gamut of application of gold catalysis is quite comprehensive to cover the synthesis of an array of important commodities like natural products, [27][28][29][30][31][32][33][34][35] drugs [36] and polymers. [37,38] Gold complexes have been documented to exhibit versatile catalytic efficiency towards a plethora of organic reactions such as CÀ H activation, [39][40][41][42][43] substitution, [44] cycloaddition, [45][46][47][48][49][50] oxidative coupling, [51,52] hydration, [53,54] oxidation, [55][56][57] hydroamination, [58,59] nucleophilic addition, [60] hydrogenation, [61] cross-coupling, [62,63] carbocyclization, [64] heterocyclization, [65][66][67][68][69][70]…”
Section: Introductionmentioning
confidence: 99%
“…The development of new methods for the synthesis of cyclopenta­[ b ]­indoles is a widely explored research area, as those structures are commonly found in many natural and biologically active compounds. , In particular, gold­(I) catalysis has emerged in the past few years as a powerful tool for the pentannulation of indoles and other N-heterocycles . Cyclization reactions triggered by electrophilic activation of an unsaturated side chain of the heterocycle, sequential gold­(I)-catalyzed hydroamination/cyclization reactions, and cascade gold­(I)-catalyzed rearrangement/cyclization processes have all successfully been employed for the pentannulation of indoles.…”
mentioning
confidence: 99%
“…Likewise, the focus of this review is to overview the gold‐catalyzed regioselective cycloisomerization of different π‐molecules owning a nucleophilic handle. Although there are a number of excellent reviews which discussed the gold catalyzed cycloisomerization reactions, [84–105] a comprehensive review on this topic that emphasizes regioselectivity is sporadic. To this end, the present review sum up the regioselective heterocyclization by activation of π‐functionality tethered nucleophiles under the catalytic action of gold.…”
Section: Introductionmentioning
confidence: 99%